Extravillous trophoblast cells-derived exosomes promote vascular smooth muscle cell migration - Salomon, Carlos; Yee, Sarah; Scholz-Romero, Katherin; Kobayashi, Miharu; Vaswani, Kanchan; Kvaskoff, David; Illanes, Sebastian E.; Mitchell, Murray D.; Rice, Gregory E. (Frontiers in Pharmacology, 2014)
Background: Vascular smooth muscle cells (VSMCs) migration is a critical process during human uterine spiral artery (SpA) remodeling and a successful pregnancy. Extravillous trophoblast cells (EVT) interact with VSMC and enhance their migration, however, the mechanisms by which EVT remodel SpA remain to be fully elucidated. We hypothesize that exosomes released from EVT promote VSMC migration. Methods: JEG-3 and HTR-8/SVneo cell lines were used as models for EVT. Cells were cultured at 37 0C and humidified under an atmosphere of 5% CO2-balanced N2 to obtain 8% O2. Cell-conditioned media were collected and exosomes (exo-JEG-3 and exo- HTR-8/SVneo) isolated by differential and buoyant density centrifugation. The effects of exo-EVT on VSMC migration were established using a real-time, live-cell imaging system (Incucyte™). Exosomal proteins where identified by mass spectrometry and submitted to bioinformatic pathway analysis (Ingenuity software) . Results: HTR-8/SVneo cells were significantly more (~30%) invasive than JEG-3 cells. HTR-8/SVneo cells released 2.6-fold more exosomes (6.39 x 108 ± 2.5 x108 particles/106 cells) compared to JEG-3 (2.86 x 108 ± 0.78 x108 particles/106 cells). VSMC migration was significantly increased in the presence of exo-JEG-3 and exo-HTR-8/SVneo compared to control (-exosomes) (21.83 ± 0.49 h and 15.57 ± 0.32, respectively, versus control 25.09 ± 0.58 h, p<0.05). Sonication completely abolished the effect of exosomes on VSMC migration. Finally, mass spectrometry analysis identified unique exosomal proteins for each EVT cell line-derived exosomes. Conclusion: The data obtained in this study are consistent with the hypothesis that the release, content and bioactivity of exosomes derived from EVT-like cell lines is cell origin-dependent and differentially regulates VSMC migration. Thus, an EVT exosomal signaling pathway may contribute to SpA remodeling by promoting the migration of VSMC out of the vessel walls.